ICE manual of geotechnical engineering geotechnical engineering principles, problematic soils and site investigation - Burland, J. B. (ICE manuals, 2012)
Written and edited by a wide selection of leading specialists, ICE Manual of Geotechnical Engineering is an authoritative and comprehensive reference resouce, providing the core geotechnical engineering principles, practical techniques, and the major questions engineers should keep in mind when dealing with real-world engineering challenges - all within a consistently coherent framework. This is the first volume of the 2 volume work: ICE Manual of Geotechnical Engineering. This volume tackles the principles and provides a solid grounding in the discipline. Furthermore this volume covers assessment of the ground and soil properties and issues.